Archaeological Monuments Contributed in Solving Social Problems - Ali, Faez Hadi; Waham, Adil Shakir (Al-Adab Journal, 2019)
Investigating the civilization of ancient Mesopotamia by means of the diversity and multiplicity of the archeological ruins and monuments of different ages, we find that they have immensely participated in changing society to a better reality through treating some aspects of is daily life. Hence, our research paper entitled “Archeological Monuments that Contributed in Solving Social Problems” came to study the influence of such monuments, as follows:First: The Artistic Monuments: Among the major artistic monuments that contributed to solving some social problems in ancient Mesopotamia are:Murals Painting.Cylinder Seals.Terracotta Plaques.Kudurru stones.Second: Architectural Monuments: Among the most important architectural monuments that contributed to solving some social problems in ancient Mesopotamia are:Circular constructions.Circular Columns.Hence, the impact of such monuments in treating some aspects of daily life is becoming evident in the ancient Mesopotamian society, taking into account that the ancient Iraqis had taken arts and architecture as one of the most significant ends and means to solve or address some of the social problems of that time.